Ethyl lauroyl arginate: An update on the antimicrobial potential and application in the food systems: a review - Ma, Yunfang; Ma, Yanqing; Chi, Lei; Wang, Shaodan; Zhang, Dianhe; Xiang, Qisen (Frontiers in Microbiology, 2023)
Lauric arginate ethyl ester (LAE), a cationic surfactant with low toxicity, displays excellent antimicrobial activity against a broad range of microorganisms. LAE has been approved as generally recognized as safe (GRAS) for widespread application in certain foods at a maximum concentration of 200 ppm. In this context, extensive research has been carried out on the application of LAE in food preservation for improving the microbiological safety and quality characteristics of various food products. This study aims to present a general review of recent research progress on the antimicrobial efficacy of LAE and its application in the food industry. It covers the physicochemical properties, antimicrobial efficacy of LAE, and the underlying mechanism of its action. This review also summarizes the application of LAE in various foods products as well as its influence on the nutritional and sensory properties of such foods. Additionally, the main factors influencing the antimicrobial efficacy of LAE are reviewed in this work, and combination strategies are provided to enhance the antimicrobial potency of LAE. Finally, the concluding remarks and possible recommendations for the future research are also presented in this review. In summary, LAE has the great potential application in the food industry. Overall, the present review intends to improve the application of LAE in food preservation.